Kānkračhāi khrū tām wutthi nai rōngrīan prathommasưksā : rāingān kānwičhai - Naphāphō̜n ʻAmō̜nlœ̄tsinthai; Khrōngkān Wičhai læ Wāngphǣn phư̄a Phatthanā Kānsưksā (Thailand) ([Bangkok] : Khrōngkān Wičhai læ Wāngphǣn phư̄a Phatthanā Kānsưksā, Samnakngān Khana Kammakān Kānsưksā hǣng Chāt, Samnak Nāyok Ratthamontrī, 1984)
Report on distribution of teachers in primary schools in Thailand, according to their educational qualifications.
In Thai.
"Wō̜phō̜ 19/27."
Includes statistical tables.
Keywords: Elementary school teachers -- Thailand; Elementary school teachers; Thailand